2021
DOI: 10.5194/amt-14-5977-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retrieval methods for planetary boundary layer height based on radiosonde data

Abstract: Abstract. Radiosonde (RS) is widely used to detect the vertical structures of the planetary boundary layer (PBL), and numerous methods have been proposed for retrieving PBL height (PBLH) from RS data. However, an algorithm that is suitable under all atmospheric conditions does not exist. This study evaluates the performance of four common PBLH algorithms under different thermodynamic stability conditions based on RS data collected from nine sites in January–December 2019. The four RS algorithms are the potenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…For example, Figure 5 shows the retrieved NRB and the corresponding calculated H PBL-MPL at XT on May 28. More complete descriptions are provided by references herein [52]. Using surface meteorological data to predict PBL structure by an empirical method [53] have significant application in the assessment of the regional PBL where no sounding observations are available.…”
Section: Airborne Measured Aerosol Optical Propertiesmentioning
confidence: 99%
“…For example, Figure 5 shows the retrieved NRB and the corresponding calculated H PBL-MPL at XT on May 28. More complete descriptions are provided by references herein [52]. Using surface meteorological data to predict PBL structure by an empirical method [53] have significant application in the assessment of the regional PBL where no sounding observations are available.…”
Section: Airborne Measured Aerosol Optical Propertiesmentioning
confidence: 99%
“…For the WRF model, the boundary-layer height is therefore estimated following the bulk Richardson number method (Vogelezang and Holtslag 1996). The method estimates the ABL height as the lowest level at which the bulk Richardson number that determines the depth and strength of mixing exceeds a critical value (R ic = 0.25) (Li et al 2021;Zhang et al 2014;Vickers and Mahrt 2004). The Richardson number method has proven to be very consistent under a wide range of atmospheric conditions, and is often used for numerical…”
Section: Regional Modelmentioning
confidence: 99%
“…The topography is high in the south and low in the north (Figure 1) [25]. According to the radiosonde data, Li et al [26] found that the mixed layer height in Jinan is low, and the diffusion capacity of the atmosphere is poor. It leads to the accumulation of pollutants and frequent air pollution events in winter [27,28].…”
Section: Observation Sitementioning
confidence: 99%